2008
DOI: 10.1007/s10338-008-0806-5
|View full text |Cite
|
Sign up to set email alerts
|

Stress intensity factor of an anti-plane crack parallel to the weak/micro-discontinuous interface in a bi-FGM composite

Abstract: The problem considered is a mode III crack lying parallel to the interface of an exponential-type functional graded material (FGM) strip bonded to a linear-type FGM substrate with infinite thickness. By applying the Fourier integral transform, the problem was reduced as a Cauchy singular integral equation with an unknown dislocation density function. The collocation method based on Chebyshev polynomials proposed by Erdogan and Gupta was used to solve the singular integral equation numerically. With the numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Many studies have suggested that 316 L stainless steel possesses impressive corrosion resistance and impact toughness [27][28][29]. Meanwhile, 2Cr13 is a widely deployed stainless steel renowned for its elevated hardness and all-encompassing performance [30,31]. The requirement for high hardness may be satisfied by blending alloy powder of 316 L and 2Cr13, and the impact toughness may be maintained through the thickness of the cladding layer.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have suggested that 316 L stainless steel possesses impressive corrosion resistance and impact toughness [27][28][29]. Meanwhile, 2Cr13 is a widely deployed stainless steel renowned for its elevated hardness and all-encompassing performance [30,31]. The requirement for high hardness may be satisfied by blending alloy powder of 316 L and 2Cr13, and the impact toughness may be maintained through the thickness of the cladding layer.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the materials within some extent of both sides of interface might be changed as functionally graded materials, i.e., the bi-material interface becomes a bi-FGM one [13][14][15]. For the bi-FGM interface, Li et al [16][17][18] brought forth the concepts of weak/micro-discontinuity and through fracture analysis found the SIF-reduction effect of the weak/micro-discontinuity on a bi-FGM interfacial crack.…”
Section: Introductionmentioning
confidence: 99%